Bacterial communities in Haemaphysalis, Dermacentor and Amblyomma ticks collected from wild boar of an Orang Asli Community in Malaysia - Lim, Fang Shiang; Khoo, Jing Jing; Tan, Kim Kee; Zainal, Nurhafiza; Loong, Shih Keng; Khor, Chee Sieng; AbuBakar, Sazaly (Ticks and tick-borne diseases, 2020)
Ticks are hematophagous vectors of arthropod-borne disease agents globally. In Malaysia, despite seroprevalence studies indicating the presence of tick-borne diseases among the indigenous people, the etiological agents of these diseases are still unclear. These indigenous people, also known as the Orang Asli, still live in forested areas with frequent contact with wildlife. Wild boar are ubiquitously found in the forested areas where the Orang Asli communities are located and are commonly hunted as a food supplement. In this study, we aim to determine the tick species parasitizing wild boar from an Orang Asli community, and explore the tick-associated bacterial communities using 16 s rRNA amplicon sequencing on the Ion Torrent PGM™ platform. A total of 72 ticks were collected from three wild boar and were morphologically identified as Haemaphysalis hystricis (n = 32), Dermacentor compactus (n = 15), Amblyomma testudinarium (n = 13), Dermacentor steini (n = 10) and Dermacentor atrosignatus (n = 2). Across all tick samples, 910 bacterial taxa were identified. Although the bacterial communities were not significantly distinct between tick species in beta-diversity analyses, Coxiella, Rickettsia and Francisella were detected at high relative abundance in H. hystricis, D. compactus and D. steini respectively. Many other bacterial genera, including those that have been described in many different tick species, were also identified, including Pseudomonas, Acinetobacter, Staphylococcus and Corynebacterium. Beta-diversity analyses also showed that the bacterial communities were separated based on the animal host from which the ticks were collected from, suggesting that the bacterial communities here may be influenced by the animal skin microflora, host blood or the environment. PCR screening confirmed the presence of Rickettsia sp. related to spotted fever group Rickettsia in some of the ticks. This study provides baseline knowledge of the microbiome of H. hystricis, D. atrosignatus, D. compactus, D. steini and A. testudinarium parasitizing wild boar in this region. The information gained in this study provides the basis to target our efforts in H. hystricis, D. compactus and D. steini for the future investigation of vector competence and the zoonotic potential for the Coxiella, Rickettsia and Francisella detected here, as well as their implications for the risks of tick-borne diseases among the Orang Asli communities.